PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA KARYAWAN TETAP PG. KREBET BARU - ULFA, MARIA (Jurnal Ilmu Manajemen (JIM), 2017)
PG. Krebet Baru Malang is a subsidiary of PT. Rajawali Nusantara Indonesia enganged in the agro industry. The company has a vision to become the industry leader in sugar cane-based global competition, then the support is required from the employees who have the skills and abilities. Where in this case required the organizational culture and organizational commitment in PG. Krebet Baru Malang. This purpose of this study is to analyze the influence of organizational culture and organizational commitment on the employee performance. Samples from this study were all employeesof the division Fabrication & Installation PG. Krebet Baru Malang which totaled 225 people. Permanent employees and using a sample probability sampling of 144 employees. For the data analysis technique used was multiple linear regression with the help of SPSS software version 23. Result of the study explained that the influence organizational culture on employee performance is significant positive. The influence of organizational commitment on the employee performance is significant positive. Organizational culture and organizational commitment have a simultaneous influence on employee performance. Keywords: Organizational Culture, Organizational Commitment, Employee Performance.